KEAMANAN REMOTE SERVER MELALUI SSH DENGAN KRIPTOSISTEM SIMETRIS - Muhammad Iqbal (Teknik Informatika Universitas Malikussaleh, 2013)
Server security is an absolute requirement to be met in the secure data by network administrator. An application to remote server is still fairly secure called secure shell (SSH). But the recent developments other parties can retrieve password from a remote login service using SSH with bruce-force method. Therefore, it needs layered security. For that to improve the security of remote ssh server using a symmetric cryptosystem that can be applied to each user who wants to remote into the server must already have a key file from the server.